2021
DOI: 10.18488/journal.23.2021.102.171.184
|View full text |Cite
|
Sign up to set email alerts
|

Non-Native English Speakers Use of Prepositions in Saudi Arabia: A Cognitive Linguistics Study

Abstract: Prepositions have a significant role in languages as users of language depend on them to produce sentence meanings and structures. This study investigates the nonlinguistic factors like cognitive, social context and experiential that are beyond linguistics and affect the use of English prepositions by Saudi non-native speakers of English. As the student's psychology to comprehend language and the centrality of the cognition are bases of cognitive linguistics, this research aimed to analyze factors that validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…However, 'Tatweer' enhances EFL learning with ICT integration (Assulaimani, 2019) that has induced positive attitudes toward EFL comprehension (Abanomey, 2013), writing (Al-Jarf, 2002, vocabulary learning (Fageeh, 2014), grammar (Al-Jarf, 2004, and overall performance (Al-Mekhlafi, 2006), no other govt. policies than SV2030 before 2016 could have aroused positive feelings and emotions in the 'highest' degree towards EFL learning and teaching as reflected in the students' priority in increasing the vocabulary for further learning in the future (Almegren, 2022). It is because the announcement has also changed Saudi nationals' vision of employment, career, and commercial activities in the future with upcoming nonconventional economic life.…”
Section: The Present Condition Of Efl Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…However, 'Tatweer' enhances EFL learning with ICT integration (Assulaimani, 2019) that has induced positive attitudes toward EFL comprehension (Abanomey, 2013), writing (Al-Jarf, 2002, vocabulary learning (Fageeh, 2014), grammar (Al-Jarf, 2004, and overall performance (Al-Mekhlafi, 2006), no other govt. policies than SV2030 before 2016 could have aroused positive feelings and emotions in the 'highest' degree towards EFL learning and teaching as reflected in the students' priority in increasing the vocabulary for further learning in the future (Almegren, 2022). It is because the announcement has also changed Saudi nationals' vision of employment, career, and commercial activities in the future with upcoming nonconventional economic life.…”
Section: The Present Condition Of Efl Learningmentioning
confidence: 99%
“…It is because Islamic principles are inherent in vision 2030 (Bunaiyan, 2019). Almegren (2022) has found that the motivations following the announcement of SV2030 are intrinsic. Unlike the other economic policies taken before, SV2030 is different in that it reforms the negative view of EFL learning as the agent of cultural infiltration.…”
Section: The Present Condition Of Efl Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…English proficiency provides Saudi Arabia with a competitive edge. In this regard, Almegren (2022) emphasizes that language plays a remarkable role in securing a position in the world economy during government-led economic revolutions. Hence, proficiency in the English language is a vital measure in Saudi Arabia's efforts toward economic diversification and transforming and advancing the country's unmatched economic growth.…”
Section: Working Knowledge Of Business Language Is Essentialmentioning
confidence: 99%